Carrier-Grade SDN-Controlled WLAN-Sharing: a Performance Evaluation of OpenFlow-Enabled Commodity- based Hardware Networking Nodes - Carmo, Maxweel S.; Souza, Thalyson L. de; Medeiros, Alisson; Neto, Augusto V.; Jardim, Sandino (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2017)
Advances in Internet of Things and smart cities approaches are resulting in an unprecedented number of devices requiring connectivity. Due to the ubiquitous presence of Wi-Fi networks, connectivity solutions obtained from residential WLAN-sharing are becoming increasingly popular, although they are still very restricted in scope, and offer a general connectivity service for users seeking to surf the Internet. We argue that with a proper network control plane and orchestration mechanisms like those provided by SDN, ISPs would be able to leverage the available Wi-Fi infrastructure so that it can offer network services that are tailored to the specific needs of mobile nodes and users. In this paper a general framework is set up to achieve this goal. As our approach explores low-cost commodity Wi-Fi access points and switches, we also include a study of the effects of SDN on a local network built on this class of equipment.